(untitled) (Research, Society and Development, 2026)
In general, woody cuttings show good results for the rooting factor in most grapevine rootstocks; however, some varieties face difficulties in this process. The present study aimed to determine the influence of plant regulators on the rooting and sprouting of stem cuttings from the ‘Paulsen 1103’ and ‘SO4’ rootstocks in a greenhouse, in the Sub-middle region of the São Francisco Valley, in the municipality of Petrolina in the State of Pernambuco (PE), Brazil. Thus, the treatments used were: T1: Control (water); T2: 500 mg L-1 of IBA; T3: 1000 mg L-1 of IBA; T4: 1500 mg L-1 of IBA; and T5: 2000 mg L-1 of IBA. The cuttings were sourced from mother plants from a commercial area, segmented to 12 to 15 centimeters in length, 1 centimeter in diameter, with 2 to 3 vegetative buds on the apical portion of the cutting. The bases of the cuttings were submerged in the IBA solutions for a period of 10 seconds. The experiment was conducted in a completely randomized design, with 5 treatments (IBA concentrations) and 5 repetitions, containing 10 cuttings per repetition, totaling 250 cuttings for each evaluated rootstock. The best results for the vegetative propagation of the ‘Paulsen 1103’ and ‘SO4’ grapevine rootstocks were observed in untreated cuttings with auxin, which showed good percentages of rooting and sprouting.